EXPERTISE IN EDUCATION: THEORETICAL ANALYSIS OF BASIC CONCEPTS - Tryhub, Ilona (The Modern Higher Education Review, 2020)
The article is devoted to theoretical analysis of basic concepts of the problem of expertise in the field of education. It is revealed that ambiguity in the definition of expertise is traced in the scientific literature, as well as the substitution of this concept by similar ones, such as monitoring, diagnostics, inspection, evaluation, audit, control, consulting, etc. It is noted that the above concepts differ in their essence, purpose, tasks, functions, purpose, objects, content, participants, application, technologies, methods, tools and output. The author specifies the essence of theoretical concepts of «expert activity in education» and «expert in the field of education».